2015
DOI: 10.1149/2.0471504jes
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Polyiosoprene Copolymer Anion Exchange Membranes by Varying Crosslinking Methods

Abstract: Anion exchange membranes (AEM) are polymer electrolytes that facilitate ion transport in alkaline fuel cells and electrochemical devices. Fabrication of mechanically durable AEMs with high ionic conductivity is a challenge. Here, a copolymer of isoprene and vinylbenzyl trimethylammonium and a terpolymer of isoprene, vinylbenzyl trimethylammonium and styrene were crosslinked by various methods, and properties, including conductivity and mechanical strength, were investigated at dry and saturated conditions. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
(66 reference statements)
2
10
0
Order By: Relevance
“…The stress–strain characteristics of HMT-PMBI, PPO-TMA, and PPO-AGO changed between drier and wetter conditions at 60 °C, which agrees with other AEMs and PEMs. , By using two different humidities, the range of mechanical properties of a film can be captured within the context of the water uptake study; a more exhaustive study was not completed as it is outside of the scope of this work. The mechanical properties of ETFE-TMA were studied previously and qualitatively agree with the changes with water content discussed here .…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The stress–strain characteristics of HMT-PMBI, PPO-TMA, and PPO-AGO changed between drier and wetter conditions at 60 °C, which agrees with other AEMs and PEMs. , By using two different humidities, the range of mechanical properties of a film can be captured within the context of the water uptake study; a more exhaustive study was not completed as it is outside of the scope of this work. The mechanical properties of ETFE-TMA were studied previously and qualitatively agree with the changes with water content discussed here .…”
Section: Resultssupporting
confidence: 71%
“…Solid lines are Park model fitting.Mechanical properties. The stress-strain characteristics of HMT-PMBI, PPO-TMA and PPO-AGO changed between drier and wetter conditions at 60 o C, which agrees with other AEMs and PEMs 76,[85][86][87][88][89]. By using two different humidities, the range of mechanical properties of a film can be captured within the context of the water uptake study; a more exhaustive study81 was not completed as it is outside of the scope of this work.…”
supporting
confidence: 68%
“…Table II summarizes the properties of all photo-crosslinked HEMs for fuel cell applications presently found in the literature. The only other photo-crosslinked HEMs synthesized via thiol-ene chemistry have been reported by Stoica et al, 12 Sollogoub et al, 13 and Vandiver et al 14 The others were polymerized and crosslinked using traditional free-radical, chain-growth mechanisms. Thiol-ene photopolymerization reactions proceed through a rapid radical mechanism, but the molecular weight builds through a step-growth mechanism, which typically produces a homogeneous polymer network.…”
Section: Resultsmentioning
confidence: 99%
“…Increased OHtransport by increasing the ion exchange capacity (IEC) of a membrane has been demonstrated; Ran et al have shown that the increase in IEC leads to larger water uptake that enhances ion transport giving a higher ionic conductivity [9]. However, the larger water uptake and dimensional swelling can compromise the mechanical strength of polymer membranes [10]. Increasing IEC does not guarantee higher conductivity, and Ertem et al have observed that the ionic conductivity increases with increasing IEC up to 1.54 mmol.g -1 and then is level at higher IECs for random copolymers of poly(isoprene) and poly(vinylbenzyl chlorine) AEMs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an in-depth study of the solvent cast membranes was not pursued further. The literature has reported an increase in membrane strength by increasing cross-linking [10,11,30,31]. Alternatively, melt pressing of the copolymer at 240 °C and 30 MPa created an insoluble membrane with controlled swelling, reduced water uptake, and greater mechanical strength.…”
Section: Introductionmentioning
confidence: 99%